Multi-environment QTL mapping identifies major genetic loci influencing soybean main stem node architecture - Ren,Honglei; Qu,Xue; Hong,Huilong; Sun,Lingling; Lamlom,Sobhi F.; Liu,Zhangxiong; Lu,Wencheng (PeerJ, 2024)
Soybean plant architecture has a significant impact on yield potential, but the genetic underpinnings of key architectural traits remain elusive. The primary objective of this study was to explore the genetic foundations underlying main stem node number (MSN) in soybeans. Recombinant inbred lines (RILs) contained a 234 individual derived from crosses between two cultivars Zhonghuang35 (ZH35) and Jindou21 (JD21) was evaluated for seed hardness across 3 years (2013, 2014, and 2015 in Gansu). Markedly, the parent varieties, shown significant differences in MSN. Also, the RIL population exhibited a wide range of genetic variation in MSN. A high-density genetic map composed of 8,078 specific-locus amplified fragment (SLAF) markers, spanning 3,480.98 centimorgans (cM) with an average inter-marker distance of 0.59 cM were used to construct linkage map. Using ICIM analysis identified a total of 23 Quantitative Trait Loci (QTLs) across the 20 chromosome, of which five QTLs were detected in multiple years in Chr.6. Notably, we identified a stable major QTL, qMSN-6-4, explaining up to 24.81% of phenotypic variation. This QTL govern seven candidate genes with potential roles in regulating MSN development in soybean, including Glyma.06G027500 with a domain of unknown function, Glyma.06G027600 involved in proton transport, Glyma.06G027700 linked to proteolysis, Glyma.06G027900 related to transcriptional regulation, and Glyma.06G028000 and Glyma.06G028050 associated with membrane functions. The RT-PCR analysis confirmed that these genes were expressed differently between the parental lines this supports the idea that they may play a role in determining MSN. Glyma.06G027500 and Glyma.06G027600 showing higher expression in JD21 leaves and nodes, while Glyma.06G027700 and Glyma.06G028000 exhibited increased expression in ZH35 stems, highlighting their distinct roles in transcription regulation, membrane activities, and protein degradation that contribute to MSN formation in soybean. This study offers valuable insights into the genetic mechanisms governing soybean MSN, providing a foundation for future research and crop improvement efforts.
Keywords: Soybean; Main stem node (MSN); QTL mapping; Candidate genes; High-density genetic map; Transcriptional factors